IDENTIFYING CRITICAL THINKING ABILITIES TO SOLVE MATHEMATICAL LITERACY PROBLEMS INTEGRATED WITH MALAY CULTURE IN JUNIOR HIGH SCHOOL STUDENTS: A STUDY ON PROBLEM-BASED LEARNING IN GEOMETRY TRANSFORMATION CONTEXT - Fadilah, Nina; Saragih, Sahat (IAIN Ambon, 2025)
This research aims to review the critical thinking skills of Junior High School (SMP) students in solving mathematics literacy problems integrated with Malay culture. Critical thinking skills are an important aspect of mathematics education because they train students to analyze, evaluate, and solve contextual problems logically and reflectively. The integration of Malay culture in mathematics literacy questions is intended to enhance the relevance of the problem context to students' lives and strengthen local cultural identity. This study uses a descriptive qualitative approach with subjects being eighth-grade students at one of the junior high schools located in the Malay cultural area. Data were obtained through a Malay culture-based mathematical literacy test and semi-structured interviews. The analysis results show that most students are able to identify important information from the questions, but still have difficulty in deeply connecting mathematical concepts with cultural contexts and in drawing logical conclusions. These findings highlight the importance of developing contextual and culturally-based literacy questions as a means to enhance students' critical thinking skills in mathematics education.